Chapter 5 Work Environment and the Origin of Ageism (2018)
All over the developed world, populations as a whole and the workforce within them are ageing. Old age discrimination in the sphere of the workplace, prejudices against older workers, and discrimination of older employees have moved into the focus of politicians, employers, trade unions, and social scientists alike. As ageism at the workplace has not only negative consequences for older workers, but also for companies’ productivity and performance, the aim should be to avoid the occurrence of ageism and mitigate its impact. In order to be able to fight ageism, it is important to trace its origins. Research on ageism in the workforce generally refers to the micro, meso and macro level determinants of ageism. Even though companies and organizations on the meso level have a great impact on the occurrence of ageist behaviour—as they provide ‘the places of work’—this level is seldom looked at systematically. This chapter therefore aims to present a conclusive overview of theories and findings in the scientific literature regarding the role of organizations/companies in cultivating, preserving or reducing ageism within them. First, the chapter looks at organizational characteristics that affect ageism, such as organizational/company structure and hierarchy, age structure of the workforce, company size, shared values and aspects of age-friendly human resource management. As organizations/companies never exist within an institutional vacuum, in a second step we subsequently identify contextual factors, such as sectorial affiliation and legal frameworks that shape and affect companies and organizational behaviour, and hence ageism within the organization.